Visual Outcomes after Implantation of Lucidis EDOF IOL - Mark Rabinovich; Gaia Ceresara; Ana Aramburu del Boz; Danial Al Khatib; Marie Crespe; Jerome Bovet (Journal of Ophthalmology)
Purpose. To evaluate the visual performance and clinical outcomes after implantation of Lucidis EDOF IOL following cataract surgery. Design. In this retrospective study, medical records from all enrolled patients were analyzed, and the following information was extracted retrospectively over 3 months following surgery. Materials and Methods. We reviewed retrospectively 181 eyes of 98 patients, who underwent cataract surgery with Lucidis extended depth of focus IOL. Results. 44 patients were males (45%) and 54 were females (55%). The average age of the study population was 68 ± 11 years. The mean preoperative BCVA (logMAR) was 0.19 ± 0.18. The mean root mean square (RMS) high order aberration (HOA) was 0.18 ± 0.1. Monocular BCVA results were 0.02 ± 0.04 (logMAR) and 0.028 ± 0.04 (logMAR) 1 month and 3 months postoperatively, respectively. Between the baseline and 1-month measures, monocular distance BCVA improved by an average of 0.17 ± 0.14 logMAR (p = 0.0001). Between the baseline and 3-month postoperative measures, monocular distance BCVA improved by an average of 0.16 ± 0.13 logMAR (p = 0.0001). Monocular UDVA 1 and 3 months postoperatively was 0.08 ± 0.1 logMAR and 0.067 ± 0.08 logMAR, respectively. 1-Month postoperative binocular UDVA was 0.036 ± 0.05 logMAR, binocular UIVA was 0.1 ± 0.08 logMAR, and binocular UNVA was 0.12 ± 0.14 logMAR. 3-Month postoperative binocular UDVA was 0.038 ± 0.05 logMAR, binocular UIVA was 0.09 ± 0.1 logMAR, and binocular UNVA was 0.16 ± 0.14 logMAR. Conclusions. Lucidis EDOF IOL achieves good visual performances in all distances.